CFD Simulation of a Drowning‐out Crystallizer for Hexanitrohexaazaisowurtzitane. Issue 6 (3rd May 2018) - Oh, Dong-Hoon; Jung, Woo-Young; Jun, Rak-Young; Lee, Chang-Ha; Oh, Min; Kim, Kwang-Joo
Abstract: Hexanitrohexaazaisowurtzitane (HNIW) is widely used for explosives, filling warheads, and solid propellants due to its high energy density and no halogen content. A pilot‐scale drowning‐out crystallizer is suggested to produce ε ‐form HNIW and computational fluid dynamics simulation (CFD) was carried out. Acetone and isopropyl alcohols served as solvent and antisolvent, respectively. Population balance with quadratic method of moment was employed for the prediction of crystal size distribution and the results were compared with experimental data. The driving force of antisolvent crystallization includes impeller speed, ratio of antisolvent to solvent, and feed flow rate. A case study with various operating conditions was performed to identify the influence of such driving forces on crystal mean diameter. The aim was a scale‐up of the antisolvent crystallization process based on experimental results and CFD simulation. Abstract : Particle size and particle morphology are important factors in the performance of solid propellants such as hexanitrohexaazaisowurtzitane (HNIW). Computational fluid dynamics simulation for an antisolvent crystallizer to produce ε ‐type HNIW crystals was carried out. The possibility of scaling up the antisolvent crystallization process based on experimental results and simulation is demonstrated.